2020
DOI: 10.2217/fvl-2019-0130
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Outbreak 2018 in District Shangla KPK; Clinical Features and Laboratory Markers of Dengue Virus Infection

Abstract: Aim: To analyze and quantify the 2018 dengue outbreak which occurred in district Shangla, Pakistan. Materials & methods: 964 suspected dengue samples were collected and examined for clinical manifestation and laboratory markers. Results: In all, 375 suspected cases were confirmed with dengue virus infection using nonstructural protein 1 (NS1) antigen, immunoglobulin M (IgM) & Immunoglobulin G (IgG) antibodies and real-time PCR whereas PCR was 92.2% sensitive. The most prevalent serotype was dengue viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…Other illnesses such as myalgia (100%), headache (61.31%), vomiting (34.63%), rashes (22.62%), and pain in the abdomen (28.91%), were identified as the highest in dengue affected persons when compared with the negative group. Our findings are inconsistent with the studies reported before, 23,28 which may be due to variance in the strain or virulence factor of the virus. But another study keeps relevant 29 …”
Section: Discussioncontrasting
confidence: 99%
“…Other illnesses such as myalgia (100%), headache (61.31%), vomiting (34.63%), rashes (22.62%), and pain in the abdomen (28.91%), were identified as the highest in dengue affected persons when compared with the negative group. Our findings are inconsistent with the studies reported before, 23,28 which may be due to variance in the strain or virulence factor of the virus. But another study keeps relevant 29 …”
Section: Discussioncontrasting
confidence: 99%
“…The infected individuals could represent several symptoms including high fever, headache, pain in joints, and myalgia 7 . In the last decade, Pkistan experienced huge outbreaks in which main serotypes DENV-2, DENV-3, DENV-4 were found in Punjab, nevertheless, in Swat and Shangla areas of KP province only DENV-2, DENV-3 was reported from 2013 to 2018 8 , 9 , 10 . Recent studies have reported that dengue virus infection is endemic in Pakistan, where the highest incidences have been reported in the monsoon season 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Few studies also showed some conflicting results [19,20]. On the other hand, several findings suggest that, safety profile of Remdesivir was also comparable or to somewhat similar to placebo [21,22].Furthermore, This Research Shows greater Remdesivir efficacy in earlier start of COVID-19 treatment.…”
Section: Resultsmentioning
confidence: 88%